Embryo manipulation in neotropical characiform fish: incubation system, anaesthetic, and PGC transplantation in Prochilodus lineatus - Carvalho, Gabriella Braga; Coelho, Geovanna Carla Zacheo; Alves, Andreoli Correia; Silva, Amanda Pereira dos Santos; Monzani, Paulo Sergio [UNESP]; Senhorini, Jose Augusto [UNESP]; Vianna, Norberto Castro; Yasui, George Shigueki [UNESP] (Cambridge Univ Press, 2022)
Primordial germ cells transplantation is a unique approach for conservation and reconstitution of endangered fish species. This study aimed to establish techniques to culture dechorionated embryos in different incubation systems and also to determine anaesthetic concentration for fish recipients in the larval stage for subsequent primordial germ cell transplantation. Intact and dechorionated embryos were divided into three incubation systems: (1) a control group with manual replacement of the solution; (2) a closed environment with high oxygen with manual replacement of the solution; and (3) constant solution recirculation. This combination resulted in six treatments. For the evaluation of anaesthetics for larvae, the concentrations evaluated were 19.5 mM, 24.4 mM, 29.3 mM, and 34.2 mM of 2-phenoxyethanol. Anaesthesia concentration and recovery at different stages were evaluated. For transplantation, primordial germ cells of Astyanax altiparanae were transplanted into anaesthetised larvae (1 dph) of Prochilodus lineatus. Better results were obtained in the recirculation system for dechorionated embryos of P. lineatus for hatching (54.18%) and normal morphology (50.06%). The 2-phenoxyethanol anaesthetic with a dose of 29.3 mM resulted in shorter induction times, in addition to the recovery time between 5 and 10 min. By using this anaesthetic concentration at transplantation, GFP-positive cells were seen in two recipients, but the cells did not proliferate. This study established an effective incubation system for the development of the dechorionated embryo and determined an effective anaesthetic concentration for P. lineatus larvae. In addition, micromanipulation and transplantation of primordial germ cells in neotropical species were conducted for the first time.
Keywords: Biotechnology; Dechorionated embryo and conservation; Micromanipulation; 2-Phenoxyethanol